PENGARUH KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Thessa Imay Sudarmo; Ugung Dwi Aryo Wibowo (Psycho Idea, 2018)
This study aims to determine whether there is influence of organizational commitment and job satisfaction toward organizational citizenship behavior (OCB) on employees of PT. Telkom Purwokerto. This research uses quantitative approach with research subject as much as 42 employees of PT. Telkom Purwokerto. Methods of data collection using organizational commitment scale, job satisfaction scale, and OCB scale. Data analysis method used using multiple linear regression model. The results showed that the organizational commitment variable had a significant effect on OCB. Job satisfaction variable has no significant effect on OCB. While the variables of organizational commitment and job satisfaction simultaneously affect to OCB.  Keywords : Job Satisfaction, Organizational Commitment, Organizational Citizenship Behavior